PENGARUH SOCIAL MEDIA MARKETING, ELECTRONIC WORD OF MOUTH (E-WOM) DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN KUE KERING PADA ONLINE SHOP NGILERABIS BAKING DI GIANYAR - Ni Kadek Tyas Rafalina; Daniel Manek (Jurnal Bakti Saraswati (JBS), 2025)
The business world is able to open up various possibilities through the expression of creativity and the development of innovation that involves a number of individuals to create goods or services that suit market needs. One sector that continues to grow today is the culinary industry, which offers a wide variety of products. Various aspects can influence consumer decisions in making purchases, including digital marketing strategies, online communication between users, and perceptions of product differentiation. This study aims to determine the influence of social media marketing, Electronic Word Of Mouth and perceptions of product variations on purchasing decisions. The study method used is quantitative. The population uses consumers who have purchased purchases at the Ngilerabis Bakingl online shop at Panjer outlets and a sample of 102 people. The basic analysis technique uses Multiple Regression Analysis. From the results of the study, it was found that social media marketing had a good and substantial influence on purchasing decisions, Electronic Word of Mouth had a good and substantial influence on purchasing decisions, and perceptions of product variety had a good and substantial influence on purchasing decisions. The advice that researchers can give is that the Ngilerabis Baking online shop should always reply and provide good responses to comments or messages sent by consumers on social media, always make interesting posts, so that interactions between consumers will run well, and also provide responses to consumer answers, make innovations in the appearance of cakes, by making cake designs that are more attractive and always offer quality products, according to what consumers expect, so that consumers will feel satisfied and are willing to provide recommendations to other consumers.